Fifty "Bab" Ballads: Much Sound and Little Sense - Gilbert, W. S. (William Schwenck), 1836-1911 (Salt Lake City, UT : Project Gutenberg, 1996)
"Fifty 'Bab' Ballads: Much Sound and Little Sense" by W. S. Gilbert is a collection of light verse published in 1876. Drawing from his childhood nickname, Gilbert crafted humorous poems that establish ridiculous premises and follow them to absurd conclusions. These satirical verses, accompanied by his own comic illustrations, showcase the "topsy-turvy" style he would later perfect in his famous operatic collaborations with Arthur Sullivan. The ballads became beloved entertainment, read aloud everywhere from private dinner parties to the House of Lords. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Bab_Ballads
Release date is 1996-12-01
Transcribed from the 1884 George Routledge and Sons editions by David Price
Keywords: English wit and humor; Humorous poetry, English